Linking Theory to Practice: A Concept Analysis - Musvipa, Mary; Ncube, Belitha; Haruzivishe, Clara; Kasu, Christine; Gwariro, Simba; Dzimir, Tafara; Ncube, Francis; Longwe, Rachel; Kanyamura, Dorothy; Mhlanga, Maxwell; Ndaimani, Augustine (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The aim of this was to clarify linking theory into practice and to identify its attributes, antecedents and consequences of linking theory into practice. Walker & Avant, (2005) model was used to clarify the concept linking theory into practice. A literature review was conducted by performing a search on scientific data base using key terms: Theory, Practice. Thirty two articles were selected of which seven were useful for this analysis. Linking theory into practice is a process with four attributes, skills training under supervision, nurse educator experience, appropriate student/ teacher relationship, non-threatening clinical environment were found to be the antecedents of these attributes. They have either positive or negative consequences for the linking theory and practice together. These findings add to the body of knowledge.